The Role of Muhammadiyah Autonomous Organizations in Developing Young Generation Leadership in the Society 5.0 Era in Bima - Ihlas Ihlas; Hendra Hendra; Amma Ainun; Uswatun Hasanah; Iyayun Amaliah; Mukmin Mukmin (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The development of the Society 5.0 era presents both challenges and opportunities for developing young generation leadership, particularly in facing the acceleration of technology, social change, and the demands of 21st-century competencies. The Muhammadiyah autonomous organization holds a strategic position as a forum for cadre development and leadership development of the young generation based on Islamic and national values. This study aims to analyze the role of the Muhammadiyah autonomous organization in developing young generation leadership in Bima in the Society 5.0 era. This study uses a qualitative approach with a descriptive-analytical research type. Data collection was conducted through in-depth interviews, observation, and documentation of the administrators and members of the Muhammadiyah autonomous organization in Bima. Data analysis was conducted using Nvivo-15 with open coding, which is presented in the form of project maps. The results of the study indicate that the Muhammadiyah autonomous organization plays an active role in developing young generation leadership through tiered cadre development, internalization of ideological values, and strengthening leadership capacity that is adaptive to technological developments and social dynamics. This study concludes that the Muhammadiyah autonomous organization contributes significantly to preparing a young generation with character, competitiveness, and responsiveness to the challenges of Society 5.0.